Marginal Sinus Arteriovenous Fistulas Mimicking Carotid Cavernous Fistulas: Diagnostic and Therapeutic Considerations - Turner, R.D.; Gonugunta, V.; Kelly, M.E.; Masaryk, T.J.; Fiorella, D.J. (American Journal of Neuroradiology, 2007)
SUMMARY: Marginal sinus fistulas (MSFs) are uncommon vascular anomalies. Occasionally, the dominant venous drainage is forced retrograde up the inferior petrosal sinus and into the cavernous sinus, causing chemosis, proptosis, and ocular hypertension, mimicking a carotid cavernous fistula. This atypical clinical presentation may lead to misdiagnosis and inappropriate hazardous treatment of an MSF. Identifying the site of the fistula and understanding the anatomy of the venous drainage are critical in providing appropriate, safe, and efficacious endovascular treatment.